1990
DOI: 10.1080/15295039009360179
|View full text |Cite
|
Sign up to set email alerts
|

Prime‐time fathers: A study in continuity and change

Abstract: This article concentrates on how women, and especially men, act as parents and spouses in domestic comedies. The first section concentrates on the background and rationale for studying the portrayals of fathers and husbands in television's domestic comedies; the second section examines the way gender (with emphasis on males) has been portrayed in these shows from the 1950s through the 1980s. The final section proposes that men are presented differently in women's fiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 4 publications
3
19
0
3
Order By: Relevance
“…This last result is also applicable to the depiction of men together with women in non-remunerated scenarios, where family scenes are the norm. These findings tie in well with research carried out by Cantor (1990) on prime-time ads and Tsai and Shumow, (2011) which emphasized the absence of the role of the nurturing father in American advertising.…”
Section: Conclusion and Further Discussionsupporting
confidence: 87%
“…This last result is also applicable to the depiction of men together with women in non-remunerated scenarios, where family scenes are the norm. These findings tie in well with research carried out by Cantor (1990) on prime-time ads and Tsai and Shumow, (2011) which emphasized the absence of the role of the nurturing father in American advertising.…”
Section: Conclusion and Further Discussionsupporting
confidence: 87%
“…However, the same study found that television viewing was correlated with the opinion that people see so few good or happy marriages in the real world that they question marriage as a way of life. The latter finding is consistent with the concern expressed by some theorists (e.g., Cantor, 1990) that exposure to media portraying marriage in an overly positive light might lead to idealized beliefs about what marriage and relationships entail, leaving youth unprepared for the hard work of relationship maintenance. It may also lead them to judge the real-life marriages that they encounter more harshly.…”
Section: Mediasupporting
confidence: 87%
“…Content-analytic studies about women on television have recurrently pointed to the stereotypical nature in which women are portrayed (Cantor, 1990;Larson, 1996). A study of prime-time television characters during 1970-1998 indicated that on television, women consistently receive less recognition than men, although there has been some change in the amount and degree of respect paid to women in this medium (Signorielli & Bacue, 1999).…”
mentioning
confidence: 99%
“…These analyses showed that women are more independent, and that mothers are more often seen outside the home. Mothers also have professions, and fathers are more caring and domesticated (Cantor, 1990;Douglas & Olson, 1996). Therefore, we included not only the total amount of television viewing in our research design, but also the amount of time spent viewing a sample of sitcoms and soaps.…”
mentioning
confidence: 99%